Sustainable Management of Mediterranean Coastal Fresh and Transitional Water Bodies: a Socio-Economic and Environmental Analysis of Changes and Trends to Enhance and Sustain Stakeholders Benefits Proceedings of the international Conference held at the End of the WADI Project (INCO-CT2005 -015226) at the University of Malta, the 5-8 November 2008 - Boffa, Jean-Marc; Conrad, Elisabeth; Nardi, Mariella; Scapini, Felicita; Cassar, Louis Francis (Proceedings e report, 2009)
This volume presents the Proceedings of the International Conference of the WADI project held in Malta, 5-8 November 2008, at the end of the project itself. The WADI project funded by the European Commission, was carried out from 2006 to 2008 by a consortium of researchers from European and Mediterranean countries, and was focused on coastal water bodies, aiming at integrating water management and the needs of all stakeholders. The Proceedings illustrate some of the outcomes of the WADI project that focused on case studies represented by water bodies in the Mediterranean coastal area.